Investigating the immune mechanism of natural products in the treatment of lung cancer - Yang, Lian; Chen, Yukun; Liu, Kaile; Chen, Yuanyuan; Zhang, Yu; Zhang, Zhanxia; Li, Hegen (Frontiers in Pharmacology, 2024)
With the deepening of people's understanding of lung cancer, the research of lung cancer immunotherapy has gradually become the focus of attention. As we all know, the treatment of many diseases relies on the rich sources, complex and varied compositions and wide range of unique biological properties of natural products.Studies have shown that natural products can exert anticancer effects by inducing tumor cell death, inhibiting tumor cell proliferation, and enhancing tumor cell autophagy.More notably, natural products can adjust and strengthen the body's immune response, which includes enhancing the function of NK cells and promoting the differentiation and proliferation of T lymphocytes. In addition, these natural products may enhance their anticancer effects by affecting inhibitory factors in the immune system, hormone levels, enzymes involved in biotransformation, and modulating other factors in the tumor microenvironment. The importance of natural products in lung cancer immunotherapy should not be underestimated. However, the specific links and correlations between natural products and lung cancer immunity are not clear enough, and further studies are urgently needed to clarify the relationship between the two. In this paper, we will focus on the correlation between natural products and lung cancer immune responses, with a view to providing new research perspectives for immunotherapy of lung cancer.